Rescaling Ruralities through the Art Project Company: Movements, Deals and Drinks. Issue 1 (2nd January 2017) - Pope, Miranda
Abstract: Taking Company: Movements, Deals, Drinks (Company) as a case study, this essay discusses implications of carrying out rural practices within urban settings. It asks how the project might rethink relationships between rural and urban settings. It looks at how these practices unpack complexes of situations, and how the project expands possibilities of mapping urban spaces in economic and social terms. To do this, it draws on Maurizio Lazzarato's understanding of enunciation as a way of understanding the project's potential to reshape dynamic relationships that the local communities have with both social and natural spaces that exist within their urban environments.